Recent Progress in Near‐Field Tip Enhancement: Principles and Applications. Issue 4 (27th January 2022) - Yin, Hailong; Zhang, Jianwei; Wang, Xuewen; Cui, Jianlei; Wang, Wenjun; Mei, Xuesong
Abstract : The micro/nano probe tip of a scanning probe microscope irradiated by a laser to induce near‐field tip enhancement (NFTE) is a state‐of‐the‐art technique of nanoscience that has witnessed significant advances in cutting‐edge research. This technique can be applied to the field of nanofabrication and nanojoining/nanomanipulation to enable the fabrication of nano‐/molecular‐scale devices. However, literature reviews are currently unavailable in the areas of nanofabrication, nanojoining, and nanomanipulation, preventing researchers from accessing a comprehensive understanding of NFTE. Herein, the essential principles and recent applications of NFTE induced by laser‐irradiated SPM probe tips are reviewed. The physical mechanism and the limiting factors are summarized in detail. The pivotal applications of NFTE in nanofabrication, nanojoining, and nanomanipulation are highlighted, along with the challenges and perspectives on NFTE for the fabrication of nanostructures. This review offers insight into NFTE for the advancement of nanotechnology. With in‐depth theoretical and experimental research, the NFTE is expected to have a significant impact on industrial applications of nanotechnology. Abstract : This work reviews the essential principles and recent applications of near‐field tip enhancement (NFTE) induced by laser‐irradiated scanning probe microscope probe tips. A detailed summary of its physical mechanism and the limiting factors is presented. The pivotal applications of NFTE in nanofabrication, nanojoining, and nanomanipulation are highlighted, along with the challenges and perspectives on NFTE.